Understanding the complexities of space anaemia in extended space missions: revelations from microgravitational odyssey - Lansiaux, Edouard; Jain, Nityanand; Yatin Chodnekar, Swarali; Siddiq, Abdelmomen; Ibrahim, Muiz; Yèche, Mathieu; Kantane, Inara (Frontiers in Physiology, 2024)
Space travel exposes astronauts to several environmental challenges, including microgravity and radiation exposure. To overcome these stressors, the body undergoes various adaptations such as cardiovascular deconditioning, fluid shifts, metabolic changes, and alterations in the state of the bone marrow. Another area of concern is the potential impact of these adaptations on erythrocyte and haemoglobin concentrations, which can lead to what is commonly referred to as space anaemia or microgravity-induced anaemia. It is known that anaemia may result in impaired physical and cognitive performance, making early detection and management crucial for the health and wellbeing of astronauts during extended space missions. However, the effects and mechanisms of space anaemia are not fully understood, and research is underway to determine the extent to which it poses a challenge to astronauts. Further research is needed to clarify the long-term effects of microgravity on the circulatory system and to investigate possible solutions to address spaceflight-induced anaemia. This article reviews the potential link between spaceflight and anaemia, based on existing evidence from simulated studies (e.g., microgravity and radiation studies) and findings from spaceflight studies (e.g., International Space Station and space shuttle missions).